'The video is an upgrade from them all': how incarcerated fathers view the affordances of video in a family literacy programme. Issue 2 (3rd April 2021) - Stickel, Tabitha; Prins, Esther; Kaiper-Marquez, Anna
ABSTRACT: In response to rising parental incarceration rates, some correctional facilities now offer family literacy and read-aloud programmes to strengthen parent–child bonds. However, the technologies used in these programmes – including older technologies such as audio and video recordings – have received little attention. Parents in the Read to Your Child/Grandchild (RYCG) programme at Pennsylvania state prisons are video recorded reading a book for their child; the book and video recording are then mailed to the child. Drawing on interview and observational data with 11 fathers at a rural prison, this study examines how fathers perceived the possibilities (affordances) of the multimodal videos. RYCG provided the only opportunity to send videos outside the prison. Moreover, the video enabled children to see their parents despite physical distance, captured a more 'lifelike' portrait of parents, was lasting and repeatable, and created another line of parent–child interaction. The perceived affordances of video reflected the restrictive prison setting and the desires of incarcerated fathers, including the desire to be recognised as a father and to show their children that they cared. Fathers' insights underscore the value of examining how people in marginalised educational sites use outmoded, receding technologies to forge new connections with loved ones.